Maternal care and offspring behaviour in three theridiid species (Araneae, Theridiidae) - Barrantes Montero, Gilbert (2009)
Maternal care is widespread in theridiids. Theridion evexum Keyserling breaks the threads in the outer layer of the egg sac to allow its spiderlings to leave the sac. Achae-aranea tesselata (Keyserling) and Anelosimus studiosus (Hentz) kill prey for their young spiderlings to feed upon. Occasionally, embryos of T. evexum die when their mother fails to break the threads of the egg sac properly, and spiderlings of A. tesselata and A. studiosus are sometimes killed when they are wrapped along with the prey when the adult spider is attacking prey. Offspring mortality is rare, suggesting that the attack behaviour is highly suppressed in spiderlings of social theridiids.